May The Laugh Be with You! The Role of Humor for Combating Radicalism to Increase National Security - Sudrajat, Sutra Yustica Sae; Almubaroq , Hikmat Zakky; Sarjito, Aris; Nano , Makmur Supriyatno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study delves into an unconventional method for combating radicalism, namely through the use of comedy or humor, with cases drawn from Indonesia and Jordan. It suggests that comedy can serve as a means of easing societal tensions and countering extremist ideologies. Utilizing a qualitative approach through literature review, the research highlights the efficacy of humor in combating extremism, particularly evidenced in the Jordanian context. This success suggests that humor could become a potent tool in the global fight against radicalism. This perspective is in line with a growing acknowledgment of the importance of non-traditional mediums, such as humor, in comprehensive strategies to combat radical ideologies, as demonstrated in a study focused on countering theTaliban. Moreover, the study identifies a lack of significant attention to the role of comedy in preventing radicalism in Indonesia. It predicts that in the future, entities such as the Indonesian Ministry of Defense and the national counter-terrorism agency may incorporate comedy or humor as a proactive measure against radicalism. The implications of this research extend to educational reforms, highlighting the need for multifaceted strategies to address the complex challenges posed by radicalism in diverse societies. The study utilizes a qualitative research method, employing a literature review approach to gather insights and evidence from existing studies and sources. It finds that comedy has been successful in combating extremism, especially in Jordan as the case. Additionally, it highlights a limited focus on the role of comedy in preventing radicalism in Indonesia.The research resulted that humor is able to become a potent weapon in the global battle against extremism. It anticipates that organizations like the Indonesian Ministry of Defense and the national counter-terrorism agency may adopt comedy as a proactive measure against early stage of radicalism in the future. Moreover, it underscores the necessity for comprehensive strategies, including educational reforms, to tackle the complexities of radicalism in varied societies.